Fifth Five-Year Plan of Orissa An Approach - Planning Commission (Planning Commission, 1972)
In spite of our efforts al planned development during the past 20 years, Orissa remains a relatively backward State in the Indian Union. This fact and also the socio-economic conditions of it's people determine our approach to the Fifth Five-Year Plan. In spite of the limitations that the concept of per capita income may have, it remains the most important composite index of an area’s development. The annual per capita income of Orissa is one of the lowest in the country.
Planning and Co-Ordination Department Government of Orissa